PTK (PENELITIAN TINDAKAN KELAS) The Influence of Cooperative Learning Model "Team Quiz" Type on Economic Learning Outcomes (An Experimental Study at SMA JAYA LANGSA - Erni Wiriani (SAJMR : Southeast Asian Journal of Management and Research, 2023)
Education plays a crucial role in shaping individuals to adapt to their environment and function effectively within society. The quality of education is key to creating high-quality human resources. Therefore, the development of learning processes that align with the needs of the times is essential, and teachers as educators have the responsibility to continuously develop relevant teaching approaches. Economics education is an integral part of education, requiring more than just knowledge transfer. Learning strategies such as Team Quiz present an interesting alternative to create an interactive and enjoyable learning environment. In this learning model, students actively engage in the learning process, encouraging them to think, discuss, and apply the concepts they have learned.